Peningkatan Layanan Administrasi Publik Melalui Pengembangan Aksesibilitas Website dan Pembuatan Video Company Profile Pada Layanan Masyarakat - Hanafi, Hanafi; Rizal Afandi, Mohammad; Ali, Ibnu (Universitas Islam Madura, 2025)
In the digital era, improving the quality of public services requires innovation in website accessibility, enabling all layers of society to easily access information. The Omben Subdistrict Office in Sampang Regency faces challenges in enhancing its service quality through digital platforms, particularly in creating a more user-friendly website. This Practical Work aims to develop website accessibility as a tool to improve public services and provide information that is more easily accessible to the community. The method applied involves Practical Work with several stages, including the first week for introducing the work environment, the second week for developing the Omben Subdistrict website, the third week for producing a company profile video, and the fourth week for compiling an article on the Practical Work report. The approach used includes website development, adding a location review feature to the map menu, and presenting information in a more structured manner. Additionally, the creation of a company profile video aims to simplify public understanding of the available services. The results of this practical work show that a more responsive website and the company profile video can enhance the public's understanding of the services provided by the Omben Subdistrict Office. Moreover, the benefits of this work for the participant's personal development include improved communication skills, decisiveness, and the ability to explain content effectively during the presentation of the Practical Work results. In terms of hard skills, the participant was able to accelerate website development, became skilled in producing the company profile video, and was able to create a website user guide.